Basaltic dykes and their xenoliths from the Gerroa–Kiama region, southern Sydney Basin, New South Wales: evidence for multiple intrusive episodes. Issue 4 (19th May 2022) - Abu-Shamma, S.; Graham, I. T.; Lennox, P.; Bann, G.; Greig, A.
Abstract: The orientation, petrography and geochemistry of numerous basaltic dykes between Kiama and Gerroa were investigated in this study. Geochemical analysis shows that the dykes range from sub-alkaline to alkaline in composition. The dykes fit into three distinct geochemical groups, with most being transitional from alkali basalts to foidites, followed by alkali basalts and lastly andesites/basaltic andesites. We suggest that three intrusive episodes occurred based on petrographic analysis and geochemical classification. The dykes contain phenocrysts of olivine, plagioclase and clinopyroxene in a fine-grained groundmass. Multiple microtextures were found, including porphyritic, glomeroporphyritic, amygdaloidal, aphanitic and intergranular. Most dykes strike northwest–southeast, two strike east–west, and four strike northeast–southwest. One dyke to the south of Boat Harbour Reserve contains numerous xenoliths, including gabbroic, granitic and charnockitic types. The gabbroic xenoliths were likely sourced from the mid-crust, whereas the granitic xenoliths were likely derived from the upper crust. Joints in the study area strike northwest–southeast, north–south, east–west and northeast–southwest. The dominant joint set strikes northwest–southeast, and secondary joint sets strike northeast–southwest. The least pervasive joint sets strike east–west and approximately north–south. The dykes intruded along long-lived inherent structural weaknesses in the host rocks, as their orientations match the orientations of dominant joint sets. Geochemically, the dykes are distinct in having an abundance of foidites, which are rare within the Sydney Basin. They are clearly different from the nearby upper Permian K-rich Gerringong Volcanics, but many of the alkali basaltic dykes are like those of the Sydney Basin, and the foidites are similar in composition to the lower Eocene Kulnura basalt on the NSW Central Coast. The orientation, geographic distribution and geochemistry of the dykes strongly suggest that the basaltic magmas have been injected through the same upper-crustal weaknesses over a protracted period. KEY POINTS: Dykes occurring between Kiama and Gerroa fall under three separate geochemical groups: alkali basalts to foidites, alkali basalts and andesites/basaltic andesites. Three intrusive episodes occurred based on petrographic analysis and geochemical classification. The dykes intruded along long-lived inherent structural weaknesses in the host rocks.